PENGARUH SUMBER ARUS LISTRIK TERHADAP NILAI TINGKAT SUARA KLAKSON BERDASARKAN STANDAR PENGUJIAN UN ECE R28 PART II - Basyari, Aziz; Alva, Sagir (Universitas Muhammadiyah Metro, 2024)
The growth of motorized vehicles in Indonesia reached 4.1% with a total number of vehicles of 136,137,451. Vehicle units operated on the highway will cause an increase in noise on the highway caused by the operation of vehicle horns. The Indonesian government has regulated horn noise quality standards through Peraturan Pemerintah Nomor 55 Tahun 2012. Indonesia has agreed to the Asean Mutual Recognation Agreement (MRA) for automotive product standards in the Asean region referring to UN ECE where for horn testing it refers to the UN ECE R28 Part II standard. From testing the horn at durations of 1, 5, 10 and 15 seconds using a battery and an idle engine, there was no significant difference in the resulting horn sound level. This research aims to ensure the source of electric current when testing the horn so that the test can run more effectively and efficiently by establishing in the operational standards the UN ECE R 28 Part II test procedure using a battery only